Pengaruh Father Involvement Terhadap Perilaku Agresif Pada Siswa Laki-Laki Usia Prasekolah Di Kota Padang Panjang - Prasetia, Hari Bayu; Primanita, Rida Yanna (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Children in preschool educational facilities are usually between four and six years old. Children begin to interact socially with more people or friends at this age. Children also begin to exhibit different behaviors. Each child exhibits aggression at different levels. Physical or verbal aggression is a common occurrence in children between the ages of 4-6 years. There are many things that can cause aggressive behavior, including personal problems originating from within the family and environmental problems arising from the environment. The family is one of the external factors that is very important for the development of this type of behavior. Father involvement at home is one of the factors suspected of being related to aggressive behavior in children. This study used a quantitative approach to collect and examine research data. A total of 86 kindergarten students in Padang Panjang City became the research sample. The right sample was selected using the cluster sampling technique. Various statistical methods were used to analyze the data. including simple linear regression tests, Using Windows SPSS 25, conducting hypothesis tests, linearity tests, and normality tests. The research findings showed a significant relationship of 38.9% between father involvement and aggressive behavior. Based on the results of this study, it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected.